Green Supply Chain Management with Life Cycle Assessment Approach for Degraded Forest Management: A Strategic-Fit Framework - Wiryawan, Liza Argarini; Ahmad Hidayat Sutawidjaya (Technium Social Sciences Journal, 2020)
Unsustainable forest management is considered as one of activities that leads to forest degradation. Together with deforestation, degraded forests are contributors to the greenhouse gas emissions from the forestry sector, so it needs to be controlled. Furthermore, degradation affects the forest’s productivity, and thus will affect the performance of the company which owns the licence for the utilization of its timber forest products. The objective of this research was to be able to identify aspects in Green Supply Chain Management and Life Cycle Assessment which are considered the most relevant to be applied in the management of degraded forest, and further to be structured in form of framework. The method used in this research is a qualitative approach with a case study PT XYZ as the holder of a Business License for the Utilization of Timber Forest Products in Natural Forest, in East Kalimantan. Research data obtained through literature studies, field observations, and interviews with key personnel in the company. Data is then analyzed through reduction and concluded. The results showed that internal supply chain activities, namely forest planning, forest development, log production, and marketing, play a significant role in the process of greening the supply chain. The proposed GSCM-LCA Framework includes Green Planning, Green Operations, Green Distributions, and Green Marketing with LCA observations focusing on evaluating and analysing environmental impacts caused by their harvesting and transportation activities. The design of the framework in this study emphasizes strategic-fit, as an effort to adjust the company resources and abilities towards the opportunities in the external environment.